Pengaruh Penambahan Magnesium Sulfat Heptahidrat dan Feri Klorida Pada BlueGreen Medium-11 Terhadap Konsentrasi Biomassa Mikroalga Tetraselmis chuii. - Bangbang Primaryadi, I Nyoman; Dewi Anggreni, Anak Agung Made; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aimd toknowthe effect of addition of magnesiumsulfate heptahydrate and ferric chloride in Blue Green Medium-11 on the production biomass of Tetraselmis chuii and tofine out the concentration of magnesium sulfate heptahydrate and ferric chloride on Blue Green medium-11 which could produce the highest biomass of Tetraselmis chuii. The Experimens was designed by a completely randomized design (CRD) with factorial pattern two factors were designent in the experient. The first factor was magnesium sulfate heptahydrate addition which was consist of three levels i.e. 0, 2, and 4g/L. The second factor was ferric chloride addition which was consist of three levels i.e. 0, 12, and 24 µM. Experiement was repeated twice times to obtain 18 units experiment. Data were analyzed by analysis of variance and if the treatment significantly affected the parameter followed by Duncan test. The addition of magnesium sulfate heptahydrat e4g/L producedin the highest biomass concentration of 4.4x10 6 cells/ml while the addition ferric chloride 24 ?m produce the highest biomass concentration of 4.3x10 6 cells/ml.
Keywords: 46